The Relationship Between Father Involvement in Parenting and Maternal Stress Levels in Mothers of Children with Intellectual Disabilities - Khaerunnisa, Erlina; Sukmawati, Ima; Roslianti, Elis; Rahayu, Yuyun; Solihah, Rosidah (Nurul Ilmi : Journal of Health Sciences and Midwifery, 2025)
Introduction: Children with intellectual disabilities require more intensive and continuous caregiving, which often places significant psychological and emotional burdens on mothers, who typically serve as the primary caregivers. The demands associated with caregiving responsibilities—ranging from managing daily activities to addressing complex emotional and behavioral needs—can result in elevated levels of maternal stress. Prolonged exposure to such stress may adversely affect a mother's physical and psychological well-being, ultimately impacting her overall quality of life. One of the contributing factors that may alleviate this burden is the active involvement of fathers in caregiving tasks. Paternal involvement is believed to offer both emotional reassurance and practical support, which can significantly ease the caregiving load carried by mothers. Objective: This study aimed to examine the relationship between paternal involvement in caregiving and maternal stress levels among families raising children with intellectual disabilities. Method: A correlational study design with a cross-sectional approach was used. The sample consisted of 49 mothers recruited using a total sampling technique. Instruments used in this research were developed by modifying the Nursing Outcome Classification (NOC) to measure paternal involvement and adopting the Parental Stress Scale to assess maternal stress. Data were analyzed using the Spearman rank correlation test with a significance level of 0.05. Result: Findings revealed that 33 mothers (67.3%) reported high paternal involvement, 11 (22.4%) moderate, and 5 (10.2%) low. Regarding maternal stress levels, 22 mothers (44.9%) experienced low stress, while 27 (55.1%) experienced moderate stress. No respondents reported high stress. Conclusion: Statistical analysis showed a significant positive correlation between paternal involvement and reduced maternal stress levels (r = 0.088; p = 0.048). These results suggest that increased paternal engagement in caregiving contributes to lower maternal stress and better maternal well-being.